Roles of dopamine receptor on chemosensory and mechanosensory primary cilia in renal epithelial cells - Upadhyay, Viralkumar; Muntean, Brian; Hwang, Jang; Kathem, Sarmed; Abou-Alaiwi, Wissam; Nauli, Surya (Frontiers in Physiology, 2014)
Dopamine plays a number of important physiological roles. However, activation of dopamine receptor type-5 (DR5) and its effect in renal epithelial cells have not been studied. Here, we show for the first time that DR5 is localized to primary cilia of LLCPK kidney cells. Renal epithelial cilia are mechanosensory organelles that sense and respond to tubular fluid-flow in the kidney. To determine the roles of DR5 and sensory cilia, we used dopamine to non-selectively and fenoldopam to selectively activate ciliary DR5. Compared to mock treatment, dopamine treated cells significantly increases the length of cilia. Fenoldopam further increases the length of cilia compared to dopamine treated cells. The increase in cilia length also increases the sensitivity of the cells in response to fluid-shear stress. The graded responses to dopamine- and fenoldopam-induced increase in cilia length further show that sensitivity to fluid-shear stress correlates to the length of cilia. Together, our studies suggest for the first time that dopamine or fenoldopam is an exciting agent that enhances structure and function of primary cilia.